2014
DOI: 10.1007/s12032-014-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and pathological features of 133 colorectal cancer patients with brain metastasis: a multicenter retrospective analysis of the Gastrointestinal Tumors Working Committee of the Turkish Oncology Group (TOG)

Abstract: Brain metastasis in colorectal cancer is highly rare. In the present study, we aimed to determine the frequency of brain metastasis in colorectal cancer patients and to establish prognostic characteristics of colorectal cancer patients with brain metastasis. In this cross-sectional study, the medical files of colorectal cancer patients with brain metastases who were definitely diagnosed by histopathologically were retrospectively reviewed. Brain metastasis was detected in 2.7 % (n = 133) of 4,864 colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Specific gene mutations in the tumor could also potentially lead to an increased risk of BM. Mutation in the PIK3CA, RAS (KRAS and NRAS) and BRAF genes have all been investigated, but mostly in smaller studies [12][13][14][15][16][17], and only RAS mutations have been shown to be significantly associated with BM in two studies [12,13]. However, the few studies examining the predictive potential of characteristics and mutations on later BM development in patients with CRC are small and retrospective.…”
Section: Introductionmentioning
confidence: 99%
“…Specific gene mutations in the tumor could also potentially lead to an increased risk of BM. Mutation in the PIK3CA, RAS (KRAS and NRAS) and BRAF genes have all been investigated, but mostly in smaller studies [12][13][14][15][16][17], and only RAS mutations have been shown to be significantly associated with BM in two studies [12,13]. However, the few studies examining the predictive potential of characteristics and mutations on later BM development in patients with CRC are small and retrospective.…”
Section: Introductionmentioning
confidence: 99%
“…There was a regular relationship between the presence of lung metastases and the subsequent development of BMs . Other extracranial metastases were reported in up to 76% of patients, including bone (5–26%), lymph nodes (7–36%) and peritoneum (3–25%) …”
Section: Resultsmentioning
confidence: 93%
“…There were 1154 males (56%) and 822 females (40%). Median age varied from 51 (41–89) to 70 (55–80) years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations